Patient-specific Guides Improve the Accuracy and Safety of Transcondylar Screw Placement—A Cadaveric Study in the Canine Humerus - Kershaw, Joshua T.; Oxley, Bill; Allen, Matthew J. (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
The goal of this study was to compare the accuracy and safety of a transcondylar screw (TCS) placed using a 3D-printed patient-specific guide (PSG) or a generic aiming device (AD). We hypothesized that PSG is more accurate (i.e., positioning and orientation closer to the optimal trajectory) and safer (reduced incidence of joint violation) than the AD.A total of seven pairs of forelimbs were allocated to PSG and AD groups. After CT scanning, the optimal TCS orientation was planned in silico by a surgical specialist, and guides were printed. Using the PSG or AD, a 2.5-mm drill hole was drilled from medial to lateral across the humeral condyle. The positioning of the “planned” and “achieved” drill holes was defined on postoperative CT. The accuracy of TCS positioning and the risk of joint penetration were then calculated for the two groups.Positioning of the entry and exit holes was significantly more accurate in the PSG group. Differences in screw angulation were not significantly different between groups. Despite the presence of an outlier (caused by incomplete seating of the PSG against the bone), 7 out of 7 screws positioned with PSG were “safe,” while 3 out of 7 from the AD group would have violated the joint.Our data confirm the technical superiority of PSG over the AD for placement of a TCS in the humeral condyle.
Keywords: computed tomography; surgical accuracy; elbow; dog; humeral intracondylar fissure; patient-specific guide